Evaluating pregnancy outcomes in women with uterine fibroids treated with high-intensity focused ultrasound: insights from a single-institution study - Min Zhao; Dan Wang; Yong Zhang; Ligang Wang (Reproductive Health)
Abstract Objective This study aims to assess the safety and effectiveness of High-Intensity Focused Ultrasound (HIFU) ablation on pregnancy outcomes among women with uterine fibroids wishing to conceive, focusing specifically on short-term pregnancy outcomes immediately following HIFU treatment. Methods A retrospective analysis was conducted on 210 women who underwent HIFU treatment (Group I) at our institution between January 2018 and December 2022 and subsequently conceived. Pregnancy outcomes were compared with two control groups: 510 patients who delivered vaginally (Group II) and 278 who underwent cesarean sections (Group III) during the same period. Statistical analyses included multivariable logistic regression to adjust for confounding factors. The study only considered outcomes related to the immediate pregnancy following HIFU treatment and did not include data on subsequent pregnancies or long-term effects. Results The natural conception rate post-HIFU was 93.81% (197/210), with a miscarriage rate of 19.05% (40/210). Group I had significantly lower rates of gestational diabetes mellitus (8.24%) and precipitate labor (0%) compared to Group II but higher rates of mild anemia (31.18%) and adherent placenta (10.59%). Compared to Group III, Group I had lower rates of gestational diabetes mellitus (8.24% vs. 20.86%) and moderate anemia (4.71% vs. 16.55%) but a higher incidence of premature rupture of membranes (18.82%). Neonates in Group I had lower birth weights compared to Groups II and III (p < 0.05), with no cases of low birth weight in Group I. Multivariable analysis identified fibroid location as a predictor of preterm birth, while maternal age and mode of delivery influenced the risk of incomplete uterine rupture. Conclusion HIFU ablation is a safe and effective fertility-preserving treatment for women with uterine fibroids, demonstrating favorable short-term pregnancy outcomes. It does not increase perinatal risks, but its impact on pregnancy duration and certain complications suggests that careful patient selection and management are crucial. Future studies should investigate the long-term effects of HIFU on subsequent pregnancies.